A hybrid joining insert for sandwich panels with pyramidal lattice truss cores. (1st June 2020) - Qi, Ge; Chen, Yun-Long; Richert, Philip; Ma, Li; Schröder, Kai-Uwe
Abstract: Sophisticated and efficient technique of sandwich attachment for composite sandwich structure assembly is imperatively required by industries. Certain types of joining inserts are widely used to carry the localized loads, but little is known regarding to the joining method for composite lattice truss core sandwich structures. In this study, a novel hybrid insert fastener, which comprises a plurality of carbon-fiber-reinforced grid cells and a metallic part, is developed for pyramidal truss core sandwich structures. Finite element models are developed to predict the failure modes and the load capabilities of different insert locations. Static pull-out and shear experiments are carried out, and the failure behaviors for each load case are discussed. The results show that the shear performance is significantly improved, and the insert position greatly affects the static pull-out behavior. An optimization of the hybrid joining insert to enhance the pull-out characteristic is addressed and verified by the finite element analysis.